Entering into a system of care: A qualitative study of carers of older community‐dwelling Australians. (6th May 2021) - Quigley, Rachel; Foster, Michele; Harvey, Desley; Ehrlich, Carolyn
Abstract: Informal carers provide the majority of care to older Australians and play an essential role in assisting older people with complex care needs to remain living in their own homes. As such, carers are increasingly faced with systemic responsibilities, including coordinating services across multifaceted health and aged care systems and negotiating treatment and supports. The aim of this study was to explore how systemic complexity and associated work is experienced by carers of older adults and what personal capacities carers draw on in managing the systemic work. A descriptive phenomenological approach guided the research. Semistructured interviews were conducted with 16 carers of community‐dwelling older adults with complex care needs recruited through a local health service. Giorgi's phenomenological data analysis methods (1997) was utilised for the data analysis. Two main themes were derived from the analysis: Becoming part of the caring system and Mastering the caring system . The findings indicate that the majority of carers perceived the work of interacting with multiple systems and services as a burden and an onerous obligation. Furthermore, change in the health or social circumstances of the older adult amplified differences in the nature of the systemic work and concomitantly revealed differences in carers' capacities. This paper reveals that the caring system is in some sense disposed to create disparities, as carers' specific capacities were integral to mastering the systemic work. An understanding of informal care work that supports older people to live in the community can assist health care professionals and service providers to better identify carer requirements and assess carer capacity to manage the work.